Information Registry System on Congenital Hypothyroidism: A Systematic Review - Morteza Ghasempour; Hamideh Ehtesham; Noushin Rostampour; Shahram Tahmasbian; Leila Shahmoradi (Mazandaran University of Medical Sciences, 2021)
Background: Congenital hypothyroidism is the most common congenital disorder of the endocrine system, leading to preventable mental retardation. Objectives: We aimed to evaluate the current status of congenital hypothyroidism information registry systems. Methods: In this systematic review 290 papers identified. A total of 254 articles were screened, of which 17 qualified articles were selected through the databases of Scopus, science direct ProQuest, PubMed, as well as the search engine Google scholar (no restriction on date of publication) up to 2020, were searched. Inclusion criteria were the Articles with the English language that examining information registry systems on congenital hypothyroidism. Articles whose full texts were not accessible, case reports, and letters to the editor had to be excluded. Results: This study showed that the primary goal of nearly half (50%) of the information registry systems for congenital hypothyroidism is to evaluate the efficiency and effectiveness of the screening program. Other information registry systems for congenital hypothyroidism have examined the epidemiology of the disease in 4 studies (23.6%), monitoring iodine deficiency in 3 studies (18%), surveillance disease in 1 study (6%), and describing the clinical and familial features of the patient in 1 study (6%). Conclusions: Few studies have been done on developing information registry systems, and most studies have focused on the use of information systems in this field. Further comprehensive reviews are recommended to investigate the infrastructure of the commission national registry and world network to record information units on congenital hypothyroidism.